Boat Models, Buoys and Board Games: Reflecting and Reliving Watermen's Work - Johnson, Paula J. (Material Culture Review, 1998)
Generations of watermen from Smith Island, Maryland, have spent their lives harvesting the seasonal round of crabs, oysters, and fish from the Chesapeake Bay. Separated from the mainland by twelve miles of open water, islanders traditionally have created their own variety of verbal and material cultural expressions. This paper explores one aspect of the island's maritime material culture — objects created by watermen, particularly those who have recently retired from full-time work on the bay. Created for various artistic and social purposes, these handmade objects, including boat models, a board game, painted figures, and reconfigured crab pot buoys, reflect their makers' strong bonds with their island home and its main occupation. The following presents these items within the context of the island's history and material culture, seeking to understand their role and significance within the community. Résumé Des générations de marins de Smith Island, au Maryland, ont passé leur vie à pêcher crabes, huîtres et poissons dans la baie de Chesapeake, de saison en saison. Coupés de la terre ferme par un bras de mer de douze milles de largeur, les habitants de l'île ont engendré un répertoire d'expressions orales et une culture matérielle qui leur sont propres. L'article qui suit examine un aspect de la culture matérielle maritime de l'île, en l'occurrence les objets façonnés par les marins, surtout ceux qui ont cessé depuis peu de travailler à temps plein dans la baie. Créés dans divers buts artistiques et sociaux, ces objets faits à la main comprennent des modèles réduits, un jeu de société, des figurines peintes et des bouées de cages à crabes sculptées. Tous évoquent les liens étroits de leurs créateurs avec leur patrie, l'île, et avec leur métier. L'article replace ces objets dans la trame historique de l'île et de sa culture matérielle, s'efforçant d'en saisir le rôle et l'importance au sein de la communauté.